Local recurrence after prone vs supine abdominoperineal excision for low rectal cancer. (30th July 2013) - Anderin, C.; Granath, F.; Martling, A.; Holm, T.
Abstract Aim Tumour‐involved circumferential resection margins (CRMs) and intra‐operative perforation (IOP) are well known risk factors for local recurrence after surgery for low rectal cancer. In conventional abdominoperineal excision (APE) the patient remains in the supine position for the perineal part of the procedure. However, turning the patient to the prone position may improve visualization which potentially might reduce the risk of involved CRMs and IOP and thus improve local control. The study was carried out to assess local recurrence rates after APE in relation to the positioning of the patient during the perineal part of the procedure. Method This cohort study includes 466 patients having APE for low rectal cancer between 2001 and December 2010. Data were retrieved from the regional rectal cancer registry in Stockholm and from a retrospective review of patient files. Results An incomplete resection was reported in 12.4% after APE in the supine position and in 6.8% after APE in the prone position (P = 0.038). Corresponding figures for IOP were 12.4% and 4.0% (P < 0.001). Prone APE was associated with a 39% relative reduction in local recurrence events compared with APE in the supine position, although the difference was not statistically significant (hazard ratio 0.61, 95% CI 0.27–1.37). Conclusion APE in the prone position reduced the incidence of incomplete resection and IOP, but the study did not find a statistically significant difference in local failure rates related to the position of the patient.